Lecturing Method and Video Learning Media Effectively Increases Knowledge and Motivation on Health Education - Wahyu Nur Pratiwi; Sri Wahyuni; Yanuar Eka Pujiastutik (STIKes Patria Husada Blitar, 2022)
The selection of health education media should be based on target tastes, broad impact, and presented in an attractive manner. Health Education on Breast Self-Examination (BSE) is generally still carried out using the conventional method, namely face-to-face (FF). This study aimed to determine the effect of health education on BSE using the Lecture Plus Animation Video Demonstration (VBL) on the knowledge and motivation of Vocational High School students. There were 80 respondents who were divided into 2 groups, 40 students in the control group with health education provided with direct FF, and the rest with VBL. The level of knowledge and motivation were obtained through a questionnaire and then the Wilcoxon signed-rank test was conducted to determine the effect of the intervention on each group, while Mann-Whitney to find out which group had better knowledge and motivation after receiving the intervention. The results showed that the Wilcoxon test in both the control and treatment groups showed p = 0.000 for the knowledge and motivation variables. Meanwhile, the Mann-Whitney test for the knowledge variable showed a p-value = 0.004 with a mean rank of 36.00 for the control group and 45.00 for the treatment group. In the motivational variable, the value of p = 0.003, and the mean rank of 46.13 in the treatment group. This meant that health education with FF methods or through VBL could increase students' knowledge and motivation, but VBL had a greater influence on increasing respondents' knowledge and motivation in doing BSE.